New species and new records of Xylosandrus Reitter, 1913 (Coleoptera: Curculionidae: Scolytinae: Xyleborini) from China - Lin, Wei; Liao, Yong-Lin; Li, You; Smith, Sarah M.; Yu, Ya-Li; Gao, Lei (Zootaxa, 2024)
Two new species of ambrosia beetles Xylosandrus Reitter, 1913 (Scolytinae: Xyleborini), Xylosandrus luokengensis Lin & Gao sp. nov. and Xylosandrus nanlingensis Lin & Gao sp. nov., from Guangdong Province, South China are described. Xylosandrus trunculus Park & Smith, 2020 is reported from China for the first time, and provincial records of all known Xylosandrus are provided.